The Musical Structure of Children and the Nature of their Development - Khojiyeva Zamirahon Quchkarovna (International Journal on Orange Technologies, 2021)
The art of music is a specific type of human activity, the function of which is to provide aesthetic services to society. In this sense, nothing can replace it. Music plays an active role in all spheres of social life. Thus, the aesthetic attitude to reality is expressed both in the musical works created by composers, and in the artistic foundations that lead to work, everyday life and human relations. The article describes the musical structure of children and their developmental characteristics.